She stoops to conquer - Goldsmith, Oliver; Miles, Dudley H. (Dudley Howe), 1881- (Boston, New York [etc.] Ginn and company, 1971)
This charming comedy has delighted audiences for over two centuries. First performed in 1773, it concerns Kate Hardcastle, a young lady who poses as a serving girl to win the heart of a young gentleman too shy to court ladies of his own class.
"Helpful books": p. xvii-xviii
Keywords: Historical -- Drama -- Adventure